Detection of Field Defects in Primary Open Angle Glaucoma Patients Using Humphrey’s Automated Perimetry – Clinical Study - Dr.D.Arpana Shaffer, Dr. B K Jain, Dr.E.Rama devi , Dr.V.Muralikrishna (International Journal of Scientific Research and Management (IJSRM), 2015)
Glaucoma is progressive, chronic optic neuropathy characterized by acquired atrophy of optic nerve and loss of retinal ganglion cells and axons. Today, glaucoma is a leading cause of irreversible blindness throughout the world. The main challenge in glaucoma facing our country is that nearly 90% of glaucoma is undetected. Although a number of competing technologies are currently available to assess loss of Nerve fibre and optic disc cupping and it may be years before all those become practically applicable in clinical practice. Today visual field analysis and assessment irrespective of Inherent subjectivity error’s in perimetry remains the most popular technique to assess the functional visual loss in patient of glaucoma.